A rare case of NUT carcinoma arising in the thyroid. Issue 5 (May 2022) - Shotton, Kieran; Walsh, Hannah; Tahir, Fawzia; Wadsley, Jonathan; Lim, Chern Beverly Brenda; Aziz, Shaniar
Abstract: We discuss the second reported case of NUT carcinoma (NC) arising in the thyroid. 1 NC is a rare and aggressive malignancy which usually arises in the midline head and neck structures. The tumour is defined cytogenetically by rearrangements of the NUTM1 gene, most commonly producing the BRD4-NUTM1 fusion oncogene. A 23-year-old-male had a neck mass excised by right hemithyroidectomy following two fine needle aspirates (Thy 3a and Thy 4). Following completion left thyroidectomy with bilateral central neck dissection, further surgery was required to excise recurrent disease from the thyroid bed and right lateral neck. This aggressive clinical course prompted molecular analysis which revealed a BRD4-NUTM1 fusion gene. The initial hemithyroidectomy diagnosis of solid variant papillary thyroid carcinoma with poorly differentiated areas was thus revised to NC. This is a rare site for NC to occur and illustrates the importance of considering this diagnosis in poorly differentiated neoplasms in the head and neck region. 1